The Observation of Biology Practical in Grade XI SMA Muhammadiyah 1 Surakarta 2015/2016 Based on Biology Practical Implementation Standard - Putri Agustina; Ike Wartini Ningsih (Bioeducation Journal, 2017)
Biology learning quality must be supported by practicum in the laboratory. Practicum will done well if all of the component on it standarized as stated in minimum standar of practicum at school. The components are laboratory and its administrator, teacher, learning process, and learning material that used. This research aim to analyze Biology practicum process in SMA Muhammadiyah 1 Surakarta based on Biology practicum processing standar at school. This research conducted in class XI SMA Muhammadiyah 1 Surakarta at second semester year 2015/2016. This research used expositori research design with qualitative approach. The data consist of laboratory condition, laboratory administratif, students worksheet, and practicum process based on observation, documentation, and interview. The result showed that: (1) biology laboratory of SMA Muhammadiyah 1 Surakarta in the good criteria (score: 80); (2) SMA Muhammadiyah 1 Surakarta do not have special laboratory administrator (laborant and laboratory technician); (3) students of SMA Muhammadiyah 1 Surakarta used students worksheet to work at laboratory; and (4) practical feasibility of class XI SMA Muhammadiyah 1 Surakarta in year 2015/2016 in the very good criteria (score: 92).